Ecological dynamics and microbial community composition of Heliotropium arboreum in the coastal ecosystems of Hainan province - Zhang, Xiaofeng; Fang, Fazhi; Sha, Linhua; Nizamani, Mir Muhammad (Frontiers in Microbiology, 2025)
Heliotropium arboreum, a resilient plant species found in the coastal ecosystems of Hainan Province, thrives in nutrient-poor, isolated habitats. This study examines the microbial community composition and ecological dynamics of H. arboreum across several islands in the South China Sea, aiming to understand how environmental factors like soil pH, nitrogen (N), and phosphorus (P) availability influence the plant's microbial communities and ecological success. The study was conducted across seven plots located on different islands, including Zhaoshu Island, Yongxing Island, and Wuzhizhou Island, among others. Soil samples were collected from three layers: 0–10 cm, 10–20 cm, and 20–30 cm. A total of 63 soil samples were processed for physicochemical analysis, measuring pH, organic matter, total nitrogen (TN), total phosphorus (TP), available phosphorus (AP), available potassium (AK), ammonium nitrogen (NH4+), and nitrate nitrogen (NO3-). Microbial DNA was extracted, amplified, and sequenced using Illumina-based platforms, producing 5,272,525 high-quality bacterial sequences and 5,273,089 fungal sequences. Bacterial communities were primarily composed of Proteobacteria (range: 29–50%), Planctomycetota, and Acidobacteriota, with significant correlations between certain bacterial genera and nutrient availability. Notably, Bryobacter (r = 0.810***) and Stenotrophobacter (r = 0.496***) showed strong positive correlations with nitrogen availability. Fungal communities were dominated by Ascomycota, followed by Basidiomycota. Preussia (r = 0.585***) and Metacordyceps (r = 0.616***) were positively correlated with nutrient availability. Diversity indices indicated that bacterial diversity was highest in pristine environments such as Zhaoshu Island (350 species), while fungal diversity was lower, with a maximum of 130 fungal species in less disturbed plots. The findings suggest that nutrient availability, particularly nitrogen and phosphorus, significantly shapes the microbial communities associated with H. arboreum. Bacterial diversity was positively correlated with nutrient-rich environments, while fungal diversity, especially Ascomycota, was more sensitive to disturbances, particularly in areas like Wuzhizhou Island and Yongxing Island, where human activity is higher. These results highlight the importance of maintaining nutrient availability and reducing human interference to preserve microbial diversity and the ecological resilience of H. arboreum in coastal ecosystems.